2019
DOI: 10.1016/j.ijpvp.2019.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the capability of the Wilshire equations in predicting uniaxial creep curves: An application to Waspaloy

Abstract: It is important to be able to predict creep strains in aeroengine so as to enable small punch disc test results to be related to uniaxial creep test results using finite element models. The capability of the Wilshire equation to interpolate creep curves was assessed using creep tests on Waspaloy. This assessment required modifying the Wilshire equation for time to strains so that the parameters of this equation could be predicted as a function of strain in a way that did not allow predicted creep curves to dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…A hat symbol will be used to designate these as estimates. Details of such a linear least squares procedure are now well documented in, for example, Evans [15]. Then values for the parameters Aj and nj in Eqs.…”
Section: Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…A hat symbol will be used to designate these as estimates. Details of such a linear least squares procedure are now well documented in, for example, Evans [15]. Then values for the parameters Aj and nj in Eqs.…”
Section: Estimationmentioning
confidence: 99%
“…Most recently, Evans and Williams [15] have incorporated Artificial Neural Network technology (ANN) into the Wilshire methodology as a solution. However, the resulting model has no closed form expression and is quite cumbersome to implement.…”
Section: Introductionmentioning
confidence: 99%
“…First, the creep behavior of Waspaloy has been shown to be dependent on applied condition with two distinct regions corresponding to the stresses above and below r Y (the yield stress). [20,21] This change in creep behavior is due to differing mechanisms of creep at different applied conditions. Whittaker et al [21] highlighted the dominance of diffusive climb at stresses below r Y with dislocation-dislocation interaction in the form of forest hardening limiting creep rates at higher stresses.…”
Section: Equivalent Uniaxial Stress For a Given Spc Forcementioning
confidence: 99%
“…[20,21] This change in creep behavior is due to differing mechanisms of creep at different applied conditions. Whittaker et al [21] highlighted the dominance of diffusive climb at stresses below r Y with dislocation-dislocation interaction in the form of forest hardening limiting creep rates at higher stresses. Birosca et al [22] showed that geometrically necessary dislocation (GND) densities are higher at the grain boundaries in Waspaloy samples crept below r Y , whereas GND densities were more uniformly spread through grains in samples crept above r Y .…”
Section: Equivalent Uniaxial Stress For a Given Spc Forcementioning
confidence: 99%
“…Recent literature has shown that failure times and minimum creep rates can be predicted reliably from accelerated test data, with the scope to further explore the ability to predict time to strains [4][5][6][7][8][9][10][11][12]. Evans and Williams [13] have modified the existing Wilshire equations so that entire creep curves can be predicted using accelerated tests at a range of conditions, and analysed the interpolated and/or extrapolated creep curves using modern statistical techniques. Given the importance of strain for developing new aeroengine materials, the aim of this paper is to build on this work by exploring the suitability of this modified Wilshire equation in predicting the times to various strains for the Nickel-based superalloy RR1000.…”
Section: Introductionmentioning
confidence: 99%